Atypical squamous cells of undetermined significance cervical cytology in the Chinese population: Age‐stratified reporting rates, high‐risk HPV testing, and immediate histologic correlation results. Issue 1 (22nd July 2020) - Tao, Xiang; Zhang, Huina; Wang, Li; Pan, Qiuzhi; Ji, Shuting; Zhou, Xianrong; Zhao, Chengquan
Abstract : Background: The US American Society of Colposcopy and Cervical Pathology guidelines for cervical cancer screening have been largely adopted worldwide. Pooled high‐risk human papillomavirus (hrHPV) testing has been routinely used to risk‐stratify women who have atypical squamous cells of undetermined significance (ASC‐US) cytology. However, it has been reported that there are distinguished differences in the distribution of hrHPV genotypes between the Chinese and American populations. Methods: The objective of this study was to analyze the age‐stratified reporting rates, hrHPV‐positive rates, and genotyping by different cytology preparation methods and hrHPV testing assays, along with the immediate histopathologic correlation of ASC‐US cytology, in the Chinese population. Results: The ASC‐US reporting rate of 1, 597, 136 Papanicolaou (Pap) tests was 4.2%, and the overall hrHPV‐positive rate was 48.7% in the ASC‐US cases. In total, 25, 338 women with ASC‐US Pap tests had immediate histologic follow‐up, and the detection rate for cervical intraepithelial neoplasia 2 and higher lesions (CIN2+) was 7.1%, including 0.6% carcinomas. Among the women who underwent hrHPV testing, CIN2+ lesions were identified in 657 of 6154 (10.7%) who had hrHPV‐positive results and in only 1.5% those who had hrHPV‐negative results. Further genotyping analysis revealed that HPV types 16 and/or 18 were commonly identified genotypes among the Chinese women who had ASC‐US cytology. Conclusions: This large‐scale study demonstrated that the hrHPV‐positive rate, the CIN2+ detection rate, and the distribution of hrHPV genotypes in Chinese women with ASC‐US cytology were essentially consistent with those from the American population, further supporting that the current and newly released 2019 American Society of Colposcopy and Cervical Pathology guidelines should be applicable to the Chinese population. Abstract : The high‐risk human papillomavirus (HPV)‐positive rate of 48.7% observed in this study is higher than that reported in most current studies. HPV types 16 (HPV16) and/or HPV18 are the common genotypes in Chinese women who have atypical squamous cells of undetermined significance cytology.